Variational and boundary value problems with perturbations - Walczak, Stanisław (Topological Methods in Nonlinear Analysis, 2001)
In the paper an optimization problem with parameters is considered. Some sufficient conditions under which the solutions of the problem continuosly depend on parameters (in the weak or the strong topology of a Banach space) are proved. Moreover, some applications to the eigenvalue and boundary value problems for differential operators are given.